GLUTAMIC ACID DECARBOXYLASE (GAD) ANTIBODIES-ASSOCIATED LIMBIC ENCEPHALITIS AND DIABETES: A CASE REPORT - Arifin, Muhamad Afiq; Yusof, Yusniza; Adam, Ida Ilyani; Lee, Ong Tien (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Glutamic acid decarboxylase (GAD) is an enzyme involved in producing the major inhibitory neurotransmitter Gamma-Aminobutyric Acid (GABA). GAD antibodies have been implicated in the pathogenesis of insulin-dependent diabetes mellitus (IDDM) and a few neurological diseases such as the case below. CASE A 24-year-old male presented with a one-week history of fever, gradual memory impairment, behavioural changes and seizure. On arrival, he was confused and disoriented. His blood glucose was 18 mmol/L, HbA1c of 12.3% with acidosis at pH 7.30, bicarbonate of 19.7, serum osmolarity of 282 mmol/L and urine FEME showed ketone 2+, glucose 3+. The lumbar puncture CSF sample was acellular with normal cerebrospinal fluid protein. Serum autoimmune and paraneoplastic panels were negative. EEG showed seizure activity at the right frontotemporal region with clinical evidence of piloerection. His brain MRI was abnormal with hyperintensity and swelling of the right medial temporal lobe. Correlating the history, EEG and radiological changes, his diagnosis is supportive of limbic encephalitis with newly diagnosed diabetes mellitus. Intravenous methylprednisolone and intravenous immunoglobulin (IVIg) were given with marked improvement of symptoms. He was discharged with regular insulin and a tapering dose of oral steroids. He had positive GAD antibodies with two readings noted at 24.45 and 18.65 IU/ml. During subsequent clinic follow-up, his HbA1c improved to 10.8% CONCLUSION Limbic encephalitis (LE) is characterized by acute or subacute development of seizure, memory impairment, irritability, hallucinations and psychiatric symptoms. Its pathogenesis is related to an inflammation of the medial temporal lobes. Non-paraneoplastic LE related to GAD antibodies should be suspected if the patient has concomitant diabetes mellitus.